BIOMASSA DAN DUGAAN CADANGAN KARBON DARI SEMAI MERANTI MERAH (Shorea montigena) DI DESA HONITETU KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Tjepy Talapessy; Johan M. Matinahoru; Ludia Siahaya (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Global climate change highlights the importance of carbon stock assessments in tropical forest ecosystems. This study aimed to quantify the biomass and carbon stock of Shorea montigena (Red Meranti) seedlings and to analyze the influence of environmental factors on seedling biomass in Honitetu Village, Inamosol District, West Seram Regency. A destructive method was applied to 30 seedlings classified into six height classes. Biomass was determined from total dry weight, and carbon stock was estimated using a conversion factor of 0.47 in accordance with SNI 7724:2019. Results showed seedling biomass ranged from 7.00 to 61.90 g, while carbon stock ranged from 3.29 to 29.09 g per individual. Simple regression confirmed that approximately 47% of dry biomass consists of carbon (R² = 1.00). Environmental factors simultaneously exerted a significant effect on biomass (R² = 0.952), with light intensity as the dominant positive factor, soil pH showing a significant negative effect, temperature a near-significant negative effect, and soil moisture not significant. These findings provide baseline data on carbon stock potential during the natural regeneration phase of S. montigena, serving as a scientific foundation for sustainable forest management and climate change mitigation strategies in Maluku’s tropical forests.